Optimasi pH dan Konsentrasi Kopresipitan pada Proses Kopresipitasi Ion Cd2+ menggunakan Al(OH)3 - Febri Andini Putri; Edi Nasra (Departemen Kimia FMIPA UNP, 2021)
Heavy metal in water content may cause serious harm to health and environment. Cd2+ as the one of trace elements contained in water poses certain challenges to be measured and handled properly. Coprecipitation of Cd2+ with Al(OH)3 as coprecipitant is characterized by Atomic Absoprtion Spectrophotometry accoording to Beer's Law. Optimum condition of this process is obtained by varying pH of the solution and coprecipitant concentration. The result indicate pH of 9 and Al3+ concentration of 0,2 M as the optimum conditions, with Cd2+ absorbed to 0,749 ppm.